Intelligent approach for accurately predicting fatigue damage in overhead highway sign structures. (December 2021) - Al Shboul, Khalid W.; Rasheed, Hayder A.; Alshareef, Husam A.
Abstract: Full-span overhead sign support structures can be found along any major highway across the US. Such structures experience different wind loading scenarios varying with time. As a result, these structures start to build up fatigue cracks within their members near the end of their fatigue life. Due to economic realities, the needed routine fatigue inspections on such highway structures can not be performed regularly. This paper is intended to present a comprehensive tool to accurately predict the remaining fatigue life of full-span overhead highway sign support structures subjected to a long and sustained wind fluctuation. Synthetic wind time histories were developed by superimposing cosine waves over a range of frequencies of 3–300 Hz and randomly generated phase angles. Kaimal spectrum was utilized to build a database of wind time histories for each daily mean wind speed along a period of 45 years in the State of Kansas. Moreover, each wind time history was modified to capture both the mean speed and high speed in each given day. After that, the wind speed vs. the number of cycle relationship, for a given time span, was extracted from the synthetic wind time history using the Rain Flow counting technique. Fatigue evaluations were conducted using axial truss member stresses extracted from a finite element solution corresponding to each wind speed in any given time range. Potential fatigue failure was assessed for each structural member after amplifying the stress range using an average dynamic amplification factor generated by integrating the frequency-response curve of harmonic excitations. These assessments evaluate the ratio of consumed fatigue cycles to ultimate fatigue cycles using Miner's rule to estimate the fatigue life. A computationally affordable simulation package was developed to carry out the generation of wind time histories, cycle counting, structural modeling, and fatigue life calculations. This package was used to evaluate the fatigue life of a non-cantilever sign structure in Wichita, Kansas. The software predicted the end-of fatigue life of two members in this structure. Accordingly, inspections of these two members revealed the existence of unnoticed severe fatigue cracks while other members did not show any sign of distress.